Fine lines : writing poetry, fiction, and drama : creative writing - Cayanan, Mark Anthony R. (Quezon City : Sibs Publishing House, Inc., 2016)
"Fine lines: Writing Poetry, Fiction, and Drama is intended to introduce the practice of writing of writing in three genres: poetry, fiction, and drama." If you have already written in all of these genres, try committing to the textbook nonetheless. Maybe there are still parts of it that can tell you something useful or, at the very least, interesting."
English text.
Keywords: Creative writing